Temporal integration of loudness measured using categorical loudness scaling and matching procedures - Valente, Daniel L.; Joshi, Suyash N.; Jesteadt, Walt (The Journal of the Acoustical Society of America, 2011)
Temporal integration of loudness of 1 kHz tones with 5 and 200 ms durations was assessed in four subjects using two loudness measurement procedures: categorical loudness scaling (CLS) and loudness matching. CLS provides a reliable and efficient procedure for collecting data on the temporal integration of loudness and previously reported nonmonotonic behavior observed at mid-sound pressure level levels is replicated with this procedure. Stimuli that are assigned to the same category are effectively matched in loudness, allowing the measurement of temporal integration with CLS without curve-fitting, interpolation, or assumptions concerning the form of the loudness growth function.